Platelet inhibitory activity and pharmacokinetics of prasugrel (CS-747) a novel thienopyridine P2Y12 inhibitor: A single ascending dose study in healthy humans - Asai, Fumitoshi; Jakubowski, Joseph A.; Naganuma, Hideo; Brandt, John T.; Matsushima, Nobuko; Hirota, Takashi; Freestone, Stephen; Winters, Kenneth J. (Platelets (Edinburgh), 2006)
We assessed the tolerability, pharmacodynamics as measured by inhibition of platelet aggregation (IPA), and pharmacokinetics of prasugrel (CS-747, LY640315), a novel thienopyridine antiplatelet agent in healthy volunteers. Twenty-four subjects were randomized into four groups of six in a double-blind, placebo-controlled trial. One subject in each group received placebo and five subjects received prasugrel orally at single doses of 2.5, 10, 30, or 75 mg. The IPA, assessed using 5 and 20 µM ADP, was periodically measured over a 7-day period by light transmission aggregometry. Plasma concentrations for three major metabolites, R-95913, R-106583, and R-100932, were measured. There were no serious adverse events and no clinically significant changes noted in any laboratory or clinical evaluations in any subject. At 1 h after prasugrel 30 and 75 mg, platelet aggregation induced by 20 µM ADP was inhibited by 43.5 ± 7.8 and 43.2 ± 15.7%, respectively, and this inhibition was significantly greater than that following placebo (5.9 ± 3.5%) (P < 0.05 for both doses). The degree of inhibition observed at 2 h was slightly higher with both prasugrel 30 and 75 mg (59.8 ± 9.9 and 57.0 ± 7.2%) and was maintained through the subsequent 22 h. At 24 h, maximal platelet aggregation induced by 20 µM ADP was reduced to ≤39% in all subjects receiving prasugrel 30 mg and to ≤38% in subjects receiving prasugrel 75 mg. Full recovery of platelet aggregation occurred between 48 h and 7 days suggesting irreversible inhibition by prasugrel and/or its metabolites. With prasugrel 2.5 and 10 mg, there was no measurable effect on platelet aggregation throughout the study (P > 0.05 for 2.5 and 10 mg prasugrel vs. placebo). With prasugrel 75 mg at 4 h postdose, there was a significant increase in the mean bleeding time compared to placebo (682 vs. 161 s; P < 0.05). Prasugrel metabolites obeyed linear pharmacokinetics and the three metabolites appeared in the plasma soon after administration, reaching maximum levels at approximately 1 h. In conclusion, prasugrel 30 and 75 mg were well tolerated and achieved a consistently high level of platelet inhibition with a fast onset of action. Errors appear in the original version of this article. These errors have since been rectified, and a corrected PDF is available here